Brewer's spent grain fermentation improves its soluble sugar and protein as well as enzymatic activities using Bacillus velezensis. (December 2021) - Zeng, Jiarui; Huang, Wenqi; Tian, Xiaofei; Hu, Xi; Wu, Zhenqiang
Graphical abstract: Highlights: Brewer's spent grain (BSG) fermentation improved its soluble sugars greatly. The soluble protein in fermented BSG was also improved effectively. High cellulase activity was obtained in BSG, especially CMCase and FPase. Ultrasonic pretreatment was beneficial to protease secretion but not to cellulase. Genome analyse showed that Bacillus velezensis K8 preferred protein to sugars. Abstract: Low nutritional value and digestive efficiency restrict the feeding application of brewer's spent grain (BSG). Bacillus velezensis has been increasingly considered a promising fermenting agent in feed production. This study aimed to investigate the fermentative characteristics of Bacillus velezensis K8 on degrading lignocellulose and increasing soluble sugar and protein in BSG. The lignocellulose contents (including cellulose, hemicellulose and lignin) decreased by 36.85 % and 27.68 % in BSG and ultrasonic-pretreated BSG (UBSG), respectively. The reducing sugar contents increased by 226.8 % and 198.1 %, and the soluble protein contents increased by 260.7 % and 258.3 % in BSG and UBSG, respectively. The arabinose, cellobiose, xylose, glucose, fructose, and xylooligosaccharides contents were significantly increased, indicating effective conversion of cellulose and hemicellulose into soluble sugars. High cellulase activity was obtained in BSG fermentation, especially CMCase and filter paper activities. Protease secretion increased but cellulase decreased, and the activities of xylanase and fructofuranosidase remained stable in UBSG fermentation. Genome analysis revealed that B. velezensis K8 possessed more amino acid-metabolism genes than carbohydrate-metabolism genes, illustrating that B. velezensis K8 preferentially utilized protein nutrients but left more sugars. These results provide a promising strategy for improving the value of grain residue in food and feed industrial applications.